Manutenção em próteses implantossuportadas: higiene oral - Santiago Júnior, Joel Ferreira [UNESP]; Lemos, Cleidiel Aparecido Araújo [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Mello, Caroline Cantieri [UNESP]; Almeida, Daniel Augusto de Faria [UNESP]; Lopes, Leonardo Ferreira de Toledo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP] (My University, 2013)
The maintenance of Implant-supported Prosthesis is essential to the success of dental implants. Therefore, the aim of the study was to conduct a review the literature addressing maintenance Implant-Supported Prosthesis in order to guide planning for the longevity of oral rehabilitation. We conducted a detailed search strategy for the Pubmed / Medline Dentistry and Oral Science, used as descriptors: “Oral Hygiene“ and “Dental Implant until July, 2013. The results were grouped together in topics (Clinical Exam and Oral Hygiene) and discussed. Conclusion: A regular maintenance program for oral patient implantprosthesis is essential to the longevity of the treatment. Different methods and devices are effective for cleansing. However one orientation (in writing) must be offered to patients, since inadequate cleaning can create regions of abrasion on the surfaces of abutments and dental implants.

A manutenção das próteses implantossuportadas é essencial para o sucesso dos implantes osseointegráveis. Assim, o objetivo deste estudo foi realizar uma revisão de literatura abordando o tema manutenção em próteses implantossuportadas com o intuito de nortear um planejamento de longevidade para as reabilitações orais. Realizou-se uma estratégia de busca detalhada para as bases de dados Pubmed/Medline e Dentistry Oral Science, foram utilizados como descritores: “Oral Hygiene“ e “Dental Implant‘‘, até Julho de 2013. Os resultados foram agrupados em tópicos (Exame Clínico e Higienização Oral) e discutidos. Concluiu-se que um programa de manutenção oral regular para o paciente com prótese implantossuportada é essencial para a longevidade do tratamento. Os diferentes métodos e dispositivos para higienização são eficientes, entretanto uma orientação cuidadosa por escrito deve ser oferecida ao paciente, para que não se crie indesejadamente regiões de abrasão nas superfícies dos implantes osseointegráveis e pilares protéticos.
Maintenance in implant-supported prostheses: oral hygiene
Keywords: Dental implants; Oral hygiene index; Maintenance; Implante dentário; Índice de higienização oral; Manutenção